Harmonizing Islam and Human Rights Through the Reconstruction of Classical Islamic Tradition - Mukharrom, Tamyiz; Abdi, Supriyanto (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
As international human rights norms are increasingly ratified by many nation-states, including in the Muslim world. There has been an increasing debate among Muslims on the universality of human rights and their compatibility with Islam. Like any religious tradition, however, Islam is open to various and frequently conflicting interpretations about its inherent normative demands. This research is a normative legal research using a legal philosophy approach. Sources of data come from literature in the form of articles, books and all materials related to the discussion. This study concludes that there are various interpretations among Muslims regarding human rights issues. On the one hand, due to the fact that the modern discourse of human rights emerged from the West, which historically closely associated with imperialism and colonialism, certain Muslim groups maintain hostile views towards human rights. On the other, there are also Muslims who, because of their intensive engagement with the West, have produced views and thoughts that tend to be accommodating or even imitative towards everything from the West including human rights issues. The article argues that philosophically harmonization between Islam and human rights is quite possible to be carried out through the reconstruction of classical Islamic traditions, so that a dialectic occurs that builds and complements one another in the future.